MetaPASS: A Web Application for Analyzing the Biological Activity Spectrum of Organic Compounds Taking into Account their Biotransformation. Issue 4 (24th November 2020) - Rudik, Anastasia; Dmitriev, Alexander; Lagunin, Alexey; Filimonov, Dmitry; Poroikov, Vladimir
Abstract: Most drug‐like compounds can interact with several pharmacological targets and exhibit complex biological activity spectra. Analysis of these spectra helps find and optimize new pharmaceutical agents or identify new uses for approved and investigational drugs (drug repurposing). Since most pharmaceuticals usually undergo biotransformation in the human body, it is reasonable during drug discovery to take into account biological activity spectra of metabolites. A new freely available MetaPASS web application (http://www.way2drug.com/metapass) has been developed for analyzing the probable biological activity spectra of drug‐like organic compounds taking into account their metabolites ‐ integrated activity profile. To obtain an integrated biological activity profile, one can create a biotransformation network for any compound or analyze known networks for more than 950 compounds from ChEBML and DrugBank. Biological activity profile prediction is based on the PASS Refined software that predicts 1, 333 biological activities with an average accuracy (IAP, calculated by leave‐one‐out cross‐validation procedure) exceeded 0.97. Abstract :